Accurate Assessment of Blood Loss During Cesarean Delivery Improves Estimate of Postoperative Hemoglobin [17B]. (May 2018) - Rubenstein, Andrew; Tully, Griffeth; Thurer, Robert
Abstract : INTRODUCTION: The need for red blood cell transfusion for patients having cesarean delivery is ideally based on an evaluation of both clinical indicators and laboratory studies. In practice, transfusions are often given to women based on estimated intraoperative blood loss (EBL) and/or the postoperative hemoglobin level. Since visual estimation is known to be inaccurate, we postulated that a more accurate determination using a novel colorimetric device would be better correlated with postoperative day one hemoglobin than visual estimation. METHODS: A formula incorporating both height and weight was used to estimate blood volume and, by including preoperative hemoglobin, red cell mass. Assuming a constant blood volume either the visual EBL (n=32) or EBL using a novel colorimetric device (Triton System™, Gauss Surgical) that incorporates a mobile application to photograph sponges and canisters and calculate their hemoglobin content (n=53) was used to predict the postoperative day one hemoglobin value in patients where either the visual estimate or colorimetric estimate was >1, 000 ml (a common definition of hemorrhage). RESULTS: The predicted postoperative day one hemoglobin level using the device was better correlated with the actual value (R squared=0.319) than the predictions using visual EBL (R squared=0.035) (P=.027). CONCLUSION: In mothers with high blood loss, EBL using the novel device was a more accurate predictor of the postoperative day one hemoglobin than visually estimated blood loss. Clinical use of this information has the potential to improve transfusion practice in cesarean delivery patients and positively impact maternal health.